We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
95
1
avatar

Please show process.

 May 12, 2019
 #1
avatar+105277 
+1

y^2 + 4x - 8y - 4  = 0

 

y^2 - 8y  =   -4x + 4            complete the square on y

 

y^2 - 8y + 16  = -4x + 4 + 16

 

(y - 4)^2  = - 4x + 20

 

-4x + 20  = (y - 4)^2

 

-4( x - 5)  = (y - 4)^2     multiply both sides by (-1/4)

 

x -5  = (-1/4)(y - 4)^2     add 5 to both sides

 

x = (-1/4)(y - 4)^2 + 5

 

cool cool cool

 May 12, 2019

8 Online Users